Evaluating the Clinical Utility of Genome Sequencing for Cytogenetically Balanced Chromosomal Abnormalities in Prenatal Diagnosis - Yu, Mullin Ho Chung; Chau, Jeffrey Fong Ting; Au, Sandy Leung Kuen; Lo, Hei Man; Yeung, Kit San; Fung, Jasmine Lee Fong; Mak, Christopher Chun Yu; Chung, Claudia Ching Yan; Chan, Kelvin Yuen Kwong; Chung, Brian Hon Yin; Kan, Anita Sik Yau (Frontiers in Genetics, 2021)
Balanced chromosomal abnormalities (BCAs) are changes in the localization or orientation of a chromosomal segment without visible gain or loss of genetic material. BCAs occur at a frequency of 1 in 500 newborns and are associated with an increased risk of multiple congenital anomalies and/or neurodevelopmental disorders, especially if it is a de novo mutation. In this pilot project, we used short read genome sequencing (GS) to retrospectively re-sequence BCAs in ten prenatal cases and compared the performance of GS with the original karyotyping. GS characterized all BCAs found by conventional karyotyping with the added benefit of precise sub-band delineation. By identifying BCA breakpoints at the nucleotide level using GS, we found disruption of OMIM genes in three cases and identified cryptic gain/loss at the breakpoints in two cases. Of these five cases, four cases reached a definitive genetic diagnosis while the other one case had a BCA interpreted as unknown clinical significance. The additional information gained from GS can change the interpretation of the BCAs and has the potential to improve the genetic counselling and perinatal management by providing a more specific genetic diagnosis. This demonstrates the added clinical utility of using GS for the diagnosis of BCAs.